Analysis of Decision-Making in The Ranks of Adhoc Election Supervisors in South Minahasa Regency - Keintjem, Eva Jeiny Greity; Taroreh, Johny; Wantah, Edwin (Technium Social Sciences Journal, 2024)
The purpose of this study is to describe and analyze how the planning, implementation, supervision, and evaluation of decision-making in adhoc election supervisors in South Minahasa Regency, North Sulawesi. Various phenomena that occur in this study are that the adhoc election supervisors in South Minahasa Regency often face dilemmas in decision-making, especially due to tight time pressure, limited resources, and interventions from various stakeholders. In addition, they are also faced with the challenge of maintaining integrity and professionalism amidst the complexity of the local political situation and conflicting interests. This phenomenon reflects how election supervisors must balance compliance with electoral regulations with the need to act quickly and effectively in the field. The current phenomenon of adhoc election supervisors in South Minahasa Regency is that there are allegations of bribery, not yet so skilled in the decision-making process, throwing responsibility to each other. This is evidenced by public distrust of adhoc election supervisors, with complaints. In the form of administrative weaknesses, coordination does not work, lack of transparency, teamwork is not effective and efficient and even the attitude of dropping each other among members is very thick. The research method used is qualitative research with purposive sampling technique. Informants are election supervisors in South Minahasa Regency. The results showed that 1) Planning in supervisory duties must be planned in accordance with the stages of supervision and existing regulations while coordinating and strengthening the regulatory understanding of the Election Supervisor with what is planned in the implementation of supervision; 2) Implementation Decision making must be in accordance with what is planned based on joint coordination so that what is planned can be implemented; 3) Supervision Decision-making is needed by adhoc supervisors in order to ensure that what is planned is in accordance with the data and what is planned; 4) Evaluating the results of supervision must be carried out by adhoc supervisors carried out in supervisory tasks from the results of tiered coordination, so that the time and results of the achievement of what is planned and decided later can be appropriate and have a positive impact on the institution.